2022
DOI: 10.1136/ijgc-2021-003006
|View full text |Cite
|
Sign up to set email alerts
|

Use of direct oral anticoagulants for postoperative venous thromboembolism prophylaxis after surgery for gynecologic malignancies

Abstract: Venous thromboembolism is a preventable cause of postoperative mortality in patients undergoing surgery for malignancy. Current standard of care based on international guideline recommends 28 days of extended thromboprophylaxis after major abdominal and pelvic surgery for malignancies with unfractionated heparin or low molecular weight heparin. Direct oral anticoagulants have been approved for the treatment of venous thromboembolism in the general population. This regimen has a significant advantage over other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…With the established safety profile of DOACs and our results showing a minimal chance of reoperation, resuming oral anticoagulants after surgery may be a safe and practical option for patients on chronic AC. Patients who were on oral anticoagulants preoperatively find it easier to return to their prior AC regimen after surgery, likely resulting in better adherence rates [ 24 , 25 , 26 ]. Moreover, we should consider treating patients after hip fracture surgery with oral anticoagulation therapy instead of LMWH, even in cases where patients were not previously on AC therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the established safety profile of DOACs and our results showing a minimal chance of reoperation, resuming oral anticoagulants after surgery may be a safe and practical option for patients on chronic AC. Patients who were on oral anticoagulants preoperatively find it easier to return to their prior AC regimen after surgery, likely resulting in better adherence rates [ 24 , 25 , 26 ]. Moreover, we should consider treating patients after hip fracture surgery with oral anticoagulation therapy instead of LMWH, even in cases where patients were not previously on AC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, however, full adherence to LMWH can be challenging, and many patients discontinue the treatment prematurely [ 23 , 24 , 25 , 26 ]. In addition, the exact duration of VTE prophylaxis following hip fracture surgery is still unknown and debatable [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of a literature review by our team which identified a gap in the literature regarding the clinical utility of DOACs as VTE prophylaxis following surgery for gynaecological malignancies, 13 we developed a survey to determine the current thromboprophylaxis practice among GOs in Australia and New Zealand, particularly their current views of DOAC use in this setting. The survey was developed by our team and consisted of 20 questions which included demographic information, current VTE prophylaxis prescribing practices (including DOAC utilisation) following various surgical procedures to manage different gynaecological tumours, and clinicians’ perceptions of safety and efficacy of DOAC use for post‐operative VTE prophylaxis (Supplementary S1).…”
Section: Methodsmentioning
confidence: 99%